Composition and Physical Stability of the Colloidal Dispersion in Veiled Virgin Olive Oil. Issue 4 (15th March 2023) - Breschi, Carlotta; Ferraro, Giovanni; Guerrini, Lorenzo; Fratini, Emiliano; Calamai, Luca; Parenti, Alessandro; Lunetti, Lorenzo; Zanoni, Bruno
Abstract: Veiled virgin olive oil (VOO) samples of nine different olive cultivars are chosen to have a wide range of physicochemical and biological properties of colloidal dispersions. The contents of proteins and phospholipids range from 40 to 190 mg kg −1 and from 70 to 200 mg kg −1, respectively. The effect of lab‐scale centrifugation on cloudy appearance is studied measuring the decrease of turbidity grade values. The time to obtain unveiled oils (20 NTU) is modeled by a logistic equation, and a clear relationship between the initial water content and the above time is observed with a different trend between two groups of the VOO samples. Four VOO samples are selected to study the aggregation phenomena of microdroplets of water, pulp particles, and olive stone fragments via optical microscopy and dynamic light scattering during lab‐scale gravity sedimentation. All VOOs are unstable with the cloudiness disappearing within the 230 days of investigation due to an overall diameter increase of cloudy components which is modeled by a power‐law equation. The VOO samples, characterized by both small diameter values of dispersed components (150–250 nm) and high values of water content, show the fastest aggregation kinetics, but they have the longest time of cloudiness stability. Practical Applications : Water content and size distribution of VOO cloudy components can be key factors to control the colloidal stability. If removal of cloudy appearance is required, centrifugation can be applied to obtain a fast oil clarification which shows a power law relationship of water content with time. Instead, if physical stability of the colloidal dispersion is required, the aggregation phenomena should be slow down through VOO processing to obtain small diameters of the cloudy components. Tuning both the water content and dispersed phase diameter in the VOO can be the first step towards the control of phenomena related to the colloidal dispersion for every olive oil processing organization, above and beyond the simple removal of cloudy appearance by filtration. Abstract : The structure of veiled virgin olive oil (VOO) is physically unstable. The characterization of structure and physical stability of the VOO colloidal dispersion should be based on measurements of water content, insoluble content, and mean diameter of the main components of cloudy appearance.